2020
DOI: 10.2138/am-2020-7162
|View full text |Cite
|
Sign up to set email alerts
|

The effects of solid-solid phase equilibria on the oxygen fugacity of the upper mantle

Abstract: Decades of study have documented several orders of magnitude variation in the oxygen fugacity (fO2) of terrestrial magmas and of mantle peridotites. This variability has commonly been attributed either to differences in the redox state of multivalent elements (e.g., Fe3+/Fe2+) in mantle sources or to processes acting on melts after segregation from their sources (e.g., crystallization or degassing). We show here that the phase equilibria of plagioclase, spinel, and garnet lherzolites of constant bulk compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 88 publications
1
17
0
Order By: Relevance
“…Several different methods of modeling f O2 in the mantle find that for a bulk mantle Fe 3+ /ΣFe ratio of 0.03 (Canil et al 1994) the shallow mantle should record f O2 of about QFM-1, which is in agreement with the continental xenolith record (e.g., Frost and McCammon 2008) but about one log unit more reduced than recorded by average MORB (Cottrell and Kelley 2011;O'Neill et al 2018;Zhang et al 2018). Jennings and Holland (2015) and Stolper et al (2020) used a THERMOCALCbased model, andStolper et al (2020) also used pMELTS, to calculate phase equilibria for a peridotite bulk composition with fixed Fe 3+ /ΣFe ratio = 0.03 at upper mantle pressures and temperatures. Jennings and Holland (2015) allowed melting to occur and Stolper et al (2020) suppressed melt formation, but both found that f O2 is lower in the spinel peridotite stability field than in the shallowest part of the garnet peridotite stability field.…”
Section: Implications Of and Supporting Evidence For A More Oxidized Morb-source Mantlementioning
confidence: 65%
See 2 more Smart Citations
“…Several different methods of modeling f O2 in the mantle find that for a bulk mantle Fe 3+ /ΣFe ratio of 0.03 (Canil et al 1994) the shallow mantle should record f O2 of about QFM-1, which is in agreement with the continental xenolith record (e.g., Frost and McCammon 2008) but about one log unit more reduced than recorded by average MORB (Cottrell and Kelley 2011;O'Neill et al 2018;Zhang et al 2018). Jennings and Holland (2015) and Stolper et al (2020) used a THERMOCALCbased model, andStolper et al (2020) also used pMELTS, to calculate phase equilibria for a peridotite bulk composition with fixed Fe 3+ /ΣFe ratio = 0.03 at upper mantle pressures and temperatures. Jennings and Holland (2015) allowed melting to occur and Stolper et al (2020) suppressed melt formation, but both found that f O2 is lower in the spinel peridotite stability field than in the shallowest part of the garnet peridotite stability field.…”
Section: Implications Of and Supporting Evidence For A More Oxidized Morb-source Mantlementioning
confidence: 65%
“…Each predict that spinel-field f O2 is in the range QFM-2 to QFM-1. The implications of Jennings and Holland (2015) and Stolper et al (2020) is that mantle with continental lithosphere-like Fe 2 O 3 concentrations are more reduced at the depths of MORB generation than QFM, which is the f O2 of the MORB source inferred from MORB themselves (Fig. 1; Cottrell and Kelley 2011;O'Neill et al 2018).…”
Section: Implications Of and Supporting Evidence For A More Oxidized Morb-source Mantlementioning
confidence: 95%
See 1 more Smart Citation
“…There are many factors that could influence the fO 2 of a partial melt of the mantle including: the major element composition of the source, which influences the mineralogy and phase equilbria under both subsolidus and supersolidus conditions as functions of P and T and could lead to variations of at least one order of magnitude in fO 2 (e.g., Jennings and Holland, 2015;Stolper et al 2020); the concentrations and oxidation states of heterovalent elements in the source, including not only Fe, but also H, C, S, and more (e.g., Frost and McCammon 2008 and references therein); and the flow of fluids through the source (e.g., Frost and McCammon 2008 and references therein). Given these and other possible factors that could influence the fO 2 levels of the mantle sources of magmas, it is difficult at this time to decode the significance of the essentially identical fO 2 levels of magmas from the C/FOZO/PREMA-rich Reunion plume source (as defined by this study and previous studies of different lavas from Reunion island, Fig.…”
Section: Oxygen Fugacities Of Reunion Island and Indian Ocean Morb Primary Magmasmentioning
confidence: 99%
“…Although a detailed comparison between thermodynamic softwares and/or databases is beyond the scope of this paper (cf. Stolper et al, 2020), the electronic annex includes a comprehensive summary of the mineral distribution, solid and melt chemistry as a function of pressure, temperature and chemical composition used in this paper and obtained with Perple X using the thermodynamic model from the use of these thermodynamic models.…”
Section: Discussionmentioning
confidence: 99%